Barometer of the business climate in Ecuador from the perspective of national and foreign investors - Guerrero, Patricia (2024)
Investors, both foreign and domestic, provide capital, technology and open investment opportunities in international markets, but their behavior is sensitive to uncertainty, political changes, economic fluctuations and other unforeseen events, and whose analysis becomes necessary for management and control. A quantitative study was conducted using questionnaires, following a business climate barometer and addressed to senior business executives to collect their assessment and the importance they attach to their companies. Five categories and 21 items with a Likert scale were established and tested on 50 entrepreneurs, and the factor analysis increased to seven categories. The results revealed that low macroeconomic stability, corruption and other political factors were identified as problematic, underscoring the complexity of the business environment; on the other hand, technological factors were evaluated as the least problematic. Therefore, this analysis contributed to a deeper understanding of the elements that make up the business climate in Ecuador, relevant to proposing effective strategies and policies; and offer an enlightening outlook to catalyze improvements and promote business resilience in the current Ecuadorian context.